In Vitro Effect of Vent Size and Spacer Thickness on Pressure Produced during Maxillary Edentulous Impression Making by Different Impression Materials - Tahereh Imani Fouladi; Abbas Fallah Tafti; Mohammad Hoseain Lotfi Kamran; Reza Mostafapour; Majid Sadegh Pourshahab; Maryam Tajaddini (Islamic Dental Association of Iran, 2016)
Background and Aim: Inappropriate transfer of pressure during final impression making in fabrication of complete denture can result in ridge resorption. This study aimed to assess the effect of vent size and spacer thickness on pressure produced during maxillary edentulous impression making by different impression materials in vitro. Materials and Methods: This experimental study was carried out using a maxillary edentulous model, two types of impression materials (regular body addition silicone and zinc oxide eugenol) and two types of trays with spacer thicknesses of 0 and 1.5 mm and each thickness with four vent sizes of 0, 0.5, 1 and 2 mm. Totally eight types of trays for each impression material (80 samples) were used. Impressions were made and transferred pressure in the first molar area of edentulous ridge and mid-palatal raphe was measured (g/mm2) by two load cells. Data were analyzed using two-way ANOVA, post hoc Tukey's test and t-test. Results: As the vent size or thickness of spacer increased, the mean pressure on maxillary edentulous ridge decreased from 59.0±2.22 to 36.8±2.50 and 98.5±5.85 to 42.8±2.11 g/mm² in ridge area and 35.0±1.66 to 19.4±1.74 and 52.1±3.80 to 22.3±1.25 g/mm² in mid-palatal raphe for regular body addition silicone and zinc oxide eugenol, respectively. Comparison between groups indicated that there were significant differences in the magnitude of pressure in use of the two materials and areas with different vent sizes and thicknesses of spacer (P< 0.001). Conclusion: Impression pressure changes significantly by change in tray design or impression material. For making impressions of an edentulous maxilla, using a tray with a 1.0 mm or larger venthole or 1.5 mm spacer thickness is recommended.